2017
DOI: 10.1186/s40478-017-0466-0
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced exosome secretion in Down syndrome brain - a protective mechanism to alleviate neuronal endosomal abnormalities

Abstract: A dysfunctional endosomal pathway and abnormally enlarged early endosomes in neurons are an early characteristic of Down syndrome (DS) and Alzheimer’s disease (AD). We have hypothesized that endosomal material can be released by endosomal multivesicular bodies (MVBs) into the extracellular space via exosomes to relieve neurons of accumulated endosomal contents when endosomal pathway function is compromised. Supporting this, we found that exosome secretion is enhanced in the brains of DS patients and a mouse mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
96
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(104 citation statements)
references
References 56 publications
8
96
0
Order By: Relevance
“…We previously demonstrated higher level of exosome release into the brain extracellular space of 12‐month‐old Ts2 mice compared to 2N controls (Gauthier et al, ). We have also shown that CD63 mRNA is upregulated in 12‐month‐old Ts2 mouse brains, and CD63 protein levels are higher in Ts2 and DS brains compared to controls and hypothesized that higher level of generation of ILVs leads to the higher level of exosome release (Gauthier et al, ). Here we confirm our hypothesis, demonstrating that trisomic murine neurons at 12 months of age produce more ILVs.…”
Section: Discussion/conclusionmentioning
confidence: 88%
See 3 more Smart Citations
“…We previously demonstrated higher level of exosome release into the brain extracellular space of 12‐month‐old Ts2 mice compared to 2N controls (Gauthier et al, ). We have also shown that CD63 mRNA is upregulated in 12‐month‐old Ts2 mouse brains, and CD63 protein levels are higher in Ts2 and DS brains compared to controls and hypothesized that higher level of generation of ILVs leads to the higher level of exosome release (Gauthier et al, ). Here we confirm our hypothesis, demonstrating that trisomic murine neurons at 12 months of age produce more ILVs.…”
Section: Discussion/conclusionmentioning
confidence: 88%
“…Here we confirm our hypothesis, demonstrating that trisomic murine neurons at 12 months of age produce more ILVs. Given that exosomes secretion was significantly enhanced also in older Ts2 mice (Gauthier et al, ), it is likely that the higher rate of ILVs formation is maintained with age. We also show that Rab35, that has a prominent role in MVBs fusion with the plasma membrane and release of ILVs via exosomes (Hsu et al, ), is enriched in endosomal/MVBs fractions, corroborating the idea that MVBs in Ts2 mice are more prone to fuse with the plasmalemma and release the cargo when compared to 2N littermates.…”
Section: Discussion/conclusionmentioning
confidence: 99%
See 2 more Smart Citations
“…As described earlier, individuals with AD and DS have dysfunctions in endosomal transport and endosomal enlargement (Cataldo et al, ; Ginsberg et al, ), a cellular pathology which may be compensated by exosomal secretion. In a recent study, Levy and colleagues support this notion with evidence that post mortem brain tissue isolated from individuals with DS expelled nearly 40% more exosomes that age‐matched non‐DS controls (Gauthier et al, ). They showed that this enhanced exosome secretion phenomenon also occurred in the TS2 mouse model of DS, which also exhibits age‐related endosome abnormalities (Levine, Saltzman, Levy, & Ginsberg, ).…”
Section: Exosome Release Mechanismsmentioning
confidence: 89%